Systems and Synthetic Biology Approaches to Engineer Fungi for Fine Chemical Production - Martins-Santana, Leonardo; Nora, Luisa C.; Sanches-Medeiros, Ananda; Lovate, Gabriel L.; Cassiano, Murilo H. A.; Silva-Rocha, Rafael (Frontiers in Bioengineering and Biotechnology, 2018)
Since the advent of systems and synthetic biology, many studies have sought to harness microbes as cell factories through genetic and metabolic engineering approaches. Yeast and filamentous fungi have been successfully harnessed to produce fine and high value-added chemical products. In this review, we present some of the most promising advances from recent years in the use of fungi for this purpose, focusing on the manipulation of fungal strains using systems and synthetic biology tools to improve metabolic flow and the flow of secondary metabolites by pathway redesign. We also review the roles of bioinformatics analysis and predictions in synthetic circuits, highlighting in silico systemic approaches to improve the efficiency of synthetic modules.